Aktualisasi Diri Tokoh Utama dalam Novel Metamorfosa Karya Nur Balqis - Ade Afmayu Nisa; Rasyimah Rasyimah; Rani Ardesi Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to describe the need for self-actualization of the main character in the novel Metamorfosa by Nur Balqis. This research applies a qualitative approach with a qualitative descriptive research type. The data in this research is quotations from sentences in the novel Metamorfosa by Nur Balqis. The data source in this research is the novel Metamorfosa by Nur Balqis. This research used reading and note-taking techniques for data collection. Data analysis was performed by reading the entire novel, noting and classifying parts of the novel related to the form of self-ctualization of the main character and describing. The research results show that the need for self-actualization is found in the metamorphosis novel by Nur Balqis. The self-actualization needs found are: the need for self-actualization in terms of ideals, desires, creativity, mental maturity and responsibility. The most dominant need for self-actualization is the need for self-actualization is desires. Meanwhile, the need for self-actualization that is least frequently found is the need for self-actualization in ideals.